Quantarctica, an integrated mapping environment for Antarctica, the Southern Ocean, and sub-Antarctic islands. (June 2021) - Matsuoka, Kenichi; Skoglund, Anders; Roth, George; de Pomereu, Jean; Griffiths, Huw; Headland, Robert; Herried, Brad; Katsumata, Katsuro; Le Brocq, Anne; Licht, Kathy; Morgan, Fraser; Neff, Peter D.; et al.
Abstract: Quantarctica (https://www.npolar.no/quantarctica ) is a geospatial data package, analysis environment, and visualization platform for the Antarctic Continent, Southern Ocean (>40 o S), and sub-Antarctic islands. Quantarctica works with the free, cross-platform Geographical Information System (GIS) software QGIS and can run without an Internet connection, making it a viable tool for fieldwork in remote areas. The data package includes basemaps, satellite imagery, terrain models, and scientific data in nine disciplines, including physical and biological sciences, environmental management, and social science. To provide a clear and responsive user experience, cartography and rendering settings are carefully prepared using colour sets that work well for typical data combinations and with consideration of users with common colour vision deficiencies. Metadata included in each dataset provides brief abstracts for non-specialists and references to the original data sources. Thus, Quantarctica provides an integrated environment to view and analyse multiple Antarctic datasets together conveniently and with a low entry barrier. Highlights: Quantarctica is the one-of-a-kind publicly available regional data package for Antarctica and Southern Ocean. Quantarctica provides user-friendly mapping environment with a free GIS software QGIS. Quantarctica includes 265 data layers in base maps, satellite imagery, terrain models, and scientific data.